A Note on Survey Research Methods Levels of Measurement: Foundational Basis for Quantitative Analysis of Survey Data - Bhandari, Prem (Dhaulagiri Journal of Sociology and Anthropology, 2022)
This research note briefly describes the levels of measurement of variables and their applications in the quantitative analysis of survey data. It first presents the concept of the measurement of variables. Second, the four levels of measurements, namely, nominal, ordinal, interval, and ratio, with examples are offered. Then, the application of these measurement levels to the statistical analysis of data at the univariate (descriptive statistics), bivariate, and multivariate (e.g., binary logistic and multiple linear regression) levels are discussed. This note is expected to be useful to the beginning (naïve) scholars for real-world application of statistical tools to analyze survey data.